Konsep Manusia dalam Pandangan Filsafat Pendidikan Islam - Muhammad Adnan (Institut Agama Islam Negeri Purwokerto, 2019)
Humans are the most perfect creatures of God. In running life, human beings are often faced with the reality of life that is not ideal. Some people do negative activities and bad things that are not in accordance with the potential good they have. This paper offers human concepts in the view of Islamic education philosophy, namely: Al-basyar, Al-insan and Al-naas. The concept of Al-Basyar tends to the human concept which can be understood that humans are creatures that have all the characteristics of humanity that are limited, such as eating, drinking, security, happiness, and so forth. The concept of Al-insan understands that humans basically have a positive potential to grow and develop both physically and mentally. The concept of Al-Naas is related to the function of humans as social beings. Humans were created as social creatures that began as a male and female partner and then developed into a tribe and nation to get to know each other